Аналіз технології когнітивного радіо в телекомунікаціях - Ткаченко, А. М. (ХНУРЕ, 2022)
The concept of cognitive radio is presented in rich detail and closely related to the concept of software defined radio (English Software Defined Radio (SDR)). Since the first publication of the concept of cognitive radio, it has been discussed more than once, speaking about the optimal variation of the radio frequency spectrum. The essence of the concept of cognitive radio lies in the so-called “Spectrum white spots” in the spectrum of radio frequencies. The stench themselves can be used as “secondary” coristuvachs for the transmission of data.